Application of energy efficient motor in Malaysian industries - Hassan, M. Y. (2000)
Electric motors are used extensively in every sector of the economy. They perform a wide range of duties throughout the industrial, commercial, residential and agricultural sectors. Motor systems are the largest industrial loads, on average accounting for more than 70 percent of all electricity consumption. Energy consumption of electric motor systems is an important economic and environmental issue. More than half the electricity generated in Malaysia is consumed by electric motor driven system applications. Therefore, industries can save considerable amounts of money on their electricity bills, if they employ motors of higher efficiency, and improve the energy efficiency of the systems driven by these motors. This paper presents test procedures to determine motor efficiency. A case study on the efficiency and improvement in energy usage by retrofitting the motors with high efficiency motors is also presented. This paper also shows the comparison in performance and cost benefits between standard motor and energy efficient motor using simple payback analysis